Evaluasi Teologis terhadap Doktrin Api Penyucian dan Tidur Jiwa dalam Perspektif Keadaan Antara - Atasia Irmansyah Dorman; Sri Dwi Harti; Gunar Sahari; Yunus Selan (JURNAL LUXNOS, 2026)
This study examines the concept of the Intermediate State theologically, particularly in relation to the doctrines of Purgatory and Soul Sleep. The purpose of this study is to evaluate whether both doctrines have a strong basis in the Bible. The method used is a qualitative theological approach through literature study and analysis of biblical texts. This study includes the concepts of Sheol, Hades, and interpretations of relevant verses. The results of the study indicate that the doctrine of Purgatory does not have a strong biblical basis and is more developed from church tradition. Meanwhile, the doctrine of Soul Sleep is also inconsistent with the biblical testimony that describes the dead remain conscious in the Intermediate State. Therefore, it is concluded that after death, humans immediately enter a state of consciousness, either in communion with God or in separation from Him, without going through an additional process of sanctification or unconsciousness.